2011
DOI: 10.5937/sjm1101073s
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurs' motivational factors: Empirical evidence from Serbia

Abstract: Entrepreneurs are playing a major role in the economy of each country on the planet. They contribute to national economies by starting up and running small and medium sized enterprises (SMEs), which make more than 95% of the total number of enterprises and which are providing jobs to more than 60% of all employees within each country. The significance of entrepreneurship for economic development oblige goverments and all other relevant institutions within each country to continue to facilitate its growth by al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
1
7
2
Order By: Relevance
“…However, similar findings were found where entrepreneurs in Sudan demonstrate the most crucial factor is to provide jobs to family members and not to increase income [35]. The least crucial factor in motivating entrepreneurs to venture in business discovered in this study were in line with previous studies which is "to have fun" [29,30,35].…”
Section: Table 1: Mean Scores For Motivation Factorssupporting
confidence: 91%
See 2 more Smart Citations
“…However, similar findings were found where entrepreneurs in Sudan demonstrate the most crucial factor is to provide jobs to family members and not to increase income [35]. The least crucial factor in motivating entrepreneurs to venture in business discovered in this study were in line with previous studies which is "to have fun" [29,30,35].…”
Section: Table 1: Mean Scores For Motivation Factorssupporting
confidence: 91%
“…Women entrepreneurs in Malaysia indicate their main motivation to venture into business is "To build a business to pass on" as it demonstrates the highest mean score of 4.40 compared to other factors. This finding however, opposed with few earlier studies [29,30,32] where all the studies revealed the most crucial factor entrepreneurs venture into business was because "to increase income". However, similar findings were found where entrepreneurs in Sudan demonstrate the most crucial factor is to provide jobs to family members and not to increase income [35].…”
Section: Table 1: Mean Scores For Motivation Factorscontrasting
confidence: 86%
See 1 more Smart Citation
“…The value of Cronbach's Alpha was 0.705, which confirmed the reliability of the instrument and then further responses up to 687 were collected (Stefanovic et al, 2011).…”
Section: Instrumentationmentioning
confidence: 53%
“…The authors are interested in applying this TRG as there are found indicators on entrepreneurial motivation indicating taking/receiving motivation variable, such as "to increase my income", "to prove I can do it", and "to be my own boss" (Benzing, Chu, & Kara, 2009;Keat & Ahmad, 2012;Robichaud, Cachon, & Haq, 2010;Stefanović, Ranković, & Prokić, 2011). This variable shows individuals' egoistic and self-interest aspects.…”
mentioning
confidence: 99%